Low energy atomic traps sluggardize the diffusion in compositionally complex refractory alloys. (April 2021) - Roy, Ankit; Munshi, Joydeep; Balasubramanian, Ganesh
Abstract: Compositionally complex alloys (CCAs) have attracted significant attention over the past decade due to their potential for exhibiting excellent mechanical properties even at elevated temperatures. The resistance to creep deformation at temperatures greater than one-half of the melting point is primarily driven by atomic diffusion, but experimental measurement of the diffusion coefficients at elevated temperatures is challenging due to the instrumentation limitations and possible oxidation of the alloy. We employ molecular dynamics simulations and first-principles calculations to examine the atomic diffusion of the various elemental species in a refractory CCA containing Mo-Ta-Ti-W-Zr as the constituents. The predictions reveal that diffusion coefficients in CCAs are slower than the corresponding diffusion in the pure metals by a factor of ~8–12, while the activation energies for the diffusion are relatively much higher. A strong attraction between unlike atomic pairs in the CCA coupled with the occurrences of low energy atomic traps due to preferential site-occupancy of the elements creates an ~1 eV energy barrier that significantly impedes atom migration. The sluggish diffusion reduces the creep deformation strain rates, increasing the resistance to creep for the CCA at high temperatures. Graphical abstract: Image 1 Highlights: Presence of multiple elements in compositionally complex refractory alloys (CCAs) retard diffusion of atoms in the lattice. Diffusion coefficients in CCAs are 8–12 times lower than the corresponding diffusion coefficients in the pure metals. Multiple elements in the lattice create atomic trap sites with ~1 eV energy barrier contributing to sluggish diffusion.